Expression of Wnt signaling agonists and antagonists in periodontitis and healthy subjects, before and after non‐surgical periodontal treatment: A systematic review - Chatzopoulos, Georgios S.; Koidou, Vasiliki P.; Wolff, Larry F. (Journal of periodontal research, 2022)
Periodontitis is a preventable and treatable multifactorial chronic inflammatory disease that can lead to irreversible periodontal destruction and tooth loss. Wnt signaling and its regulators play an important role in periodontal inflammation, destruction, regeneration, and reconstruction. This systematic review aimed at investigating the involvement of Wnt signaling agonists and antagonists in periodontitis and healthy subjects, before and after periodontal treatment. Electronic searches were carried out using MEDLINE/PubMed, EMBASE, and Cochrane Library databases in addition to hand searches. Studies having different designs assessing the levels of Wnt signaling antagonist and agonist levels in gingival crevicular fluid, serum, and tissue in patients diagnosed with periodontitis or gingivitis, compared with healthy individuals were included. In addition, studies compared these levels in periodontitis patients before and after non‐surgical periodontal therapy were also eligible. Sixteen studies met the eligibility criteria. Sclerostin (SOST) has been mainly investigated in the literature (8 publications). Sclerostin (5 studies), Wnt‐5a (2 studies), secreted frizzled‐related protein 1 (SFRP1) (3 studies), and β‐catenin (3 studies) show increased levels in periodontitis compared with periodontal health. Strong correlations between marker levels and periodontal clinical parameters were identified for SOST (5 studies), SFRP1 (2 studies), and β‐catenin (2 studies). SOST (3 studies) and SFRP1 (1 study) levels significantly decrease following non‐surgical periodontal treatment. The present systematic review demonstrated an association between Wnt signaling agonist and antagonist levels and periodontitis. Wnt agonists and antagonists may serve as valuable diagnostic and prognostic markers for periodontitis onset and progression. Further case–control and longitudinal studies should be conducted for different Wnt signaling agonists and antagonists.